2023
DOI: 10.1038/s41598-023-29421-2
|View full text |Cite
|
Sign up to set email alerts
|

Ovicidal toxicity of plant essential oils and their major constituents against two mosquito vectors and their non-target aquatic predators

Abstract: Plant essential oil (EO) is a natural alternative to synthetic chemical insecticides for mosquito control. EOs from Citrus aurantium L., Cymbopogon citratus (Stapf.), and Cinnamomum verum (J. Presl.) were selected for topical assay of their ovicidal activity against Aedes aegypti (Linnaeus) and Aedes albopictus (Skuse). Their efficacy was compared to that of 1% (w/w) temephos. In addition, their non-toxicity against aquatic mosquito predators, Poecilia latipinna and Poecilia reticulata, was tested. Found by GC… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
20
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 45 publications
5
20
0
Order By: Relevance
“…germanica indicated that trans -cinnamaldehyde is the main factor responsible for the insecticidal activity of cinnamon EO. This is consistent with the previously reported strong insecticidal activity of trans -cinnamaldehyde against a variety of pests. , …”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…germanica indicated that trans -cinnamaldehyde is the main factor responsible for the insecticidal activity of cinnamon EO. This is consistent with the previously reported strong insecticidal activity of trans -cinnamaldehyde against a variety of pests. , …”
Section: Discussionsupporting
confidence: 93%
“…This is consistent with the previously reported strong insecticidal activity of trans-cinnamaldehyde against a variety of pests. 25,26 Eugenol and β-caryophyllene are the most representative compounds of clove EO. 27 Several reports indicated that eugenol has shown some insecticidal activity against various insects.…”
Section: ■ Discussionmentioning
confidence: 99%
“…Root extracted oils from Hedychium stenopetalum, Hedychium villosum (Huong et al 2022). Bark extracted essential oil from cinnamon (Mustapa et al 2023), Cinnamomum verum (Moungthipmalai et al 2023). Number of research author's reports implies the remarkable biological activity of essential oil (Al-Keridis 2017;Vasantha-Srinivasan et al 2018;De Souza et al 2019;Thanigaivel et al 2019;Yaméogo et al 2021).…”
Section: Essential Oils As Vector Control Agentmentioning
confidence: 99%
“…aegypti and Ae . albopictus eggs) but were non-toxic to the tested non-target predators ( Poecilia latipinna and Poecilia reticulata ) [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Several combinations of EOs and their major constituents had high potential for use as green repellents against houseflies in that they were, at the time, more effective than DEET, a popular synthetic repellent, and they were safer repellents for humans, environmentally friendly, and non-toxic to non-target predators [ 19 , 20 ]. Consequently, this study was motivated to investigate the adult housefly and the repellency incurred by single-component and combinations of lemongrass and star anise EOs and their main active constituents.…”
Section: Introductionmentioning
confidence: 99%